21z-3(2z+14)=14z+11

Simple and best practice solution for 21z-3(2z+14)=14z+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21z-3(2z+14)=14z+11 equation:


Simplifying
21z + -3(2z + 14) = 14z + 11

Reorder the terms:
21z + -3(14 + 2z) = 14z + 11
21z + (14 * -3 + 2z * -3) = 14z + 11
21z + (-42 + -6z) = 14z + 11

Reorder the terms:
-42 + 21z + -6z = 14z + 11

Combine like terms: 21z + -6z = 15z
-42 + 15z = 14z + 11

Reorder the terms:
-42 + 15z = 11 + 14z

Solving
-42 + 15z = 11 + 14z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-14z' to each side of the equation.
-42 + 15z + -14z = 11 + 14z + -14z

Combine like terms: 15z + -14z = 1z
-42 + 1z = 11 + 14z + -14z

Combine like terms: 14z + -14z = 0
-42 + 1z = 11 + 0
-42 + 1z = 11

Add '42' to each side of the equation.
-42 + 42 + 1z = 11 + 42

Combine like terms: -42 + 42 = 0
0 + 1z = 11 + 42
1z = 11 + 42

Combine like terms: 11 + 42 = 53
1z = 53

Divide each side by '1'.
z = 53

Simplifying
z = 53

See similar equations:

| 4x+3+6x=17 | | 5(x-9)=4x | | 5x-45=4x | | 4x^4-8x^3+5x^2-x-1=0 | | (4x^3-8x^2+5x-1)=0 | | 8y-9x-1=0 | | 15p+40= | | 5-p=-2 | | -19v-18=-16v+3 | | -19v-18=16v+3 | | 4v^3+6v^2-4v=0 | | 2y^2=32 | | 3x-7=9x+18 | | 2x+10=3x-22 | | 5(3n-1)=80 | | S=35+14t-2t | | rX^2-37x-36=0 | | 7x+1=3x+19 | | 7x-1=3x+19 | | 2x+(x-6)=3x-(4x-6) | | 18=3(25t+2) | | P(4)=x^3-4x^2+8 | | 6=10-2a | | 6x+1=x+7 | | 4=x-0.6 | | x^2(x^2+1)-3(2x^2+1)+9=0 | | 6t^2-38t-28=0 | | X(x+15)=95 | | 12x-9=7x+4x-2 | | 12x-9=7x | | -2(x+3)-4(x-5)=-2x+1 | | -2(-x+3)-4(x-5)=2x+1 |

Equations solver categories